Honey Buzzard Pernis apivorus nest‐site selection in relation to habitat and the distribution of Goshawks Accipiter gentilis. (16th March 2013) - Gamauf, Anita; Tebb, Graham; Nemeth, Erwin; Arroyo, Beatriz
<x xml:space="preserve">Abstract</x> The selection of a suitable nest‐site is critical for successful reproduction. Species' preferences for nest‐sites have presumably evolved in relation to local habitat resources and/or interactions with other species. The importance of these two components in the nest‐site selection of the Eurasian Honey Buzzard Pernis apivorus was assessed in two study areas in eastern Austria. There was almost no difference in macro‐ and micro‐habitat features between nest‐sites and random plots, suggesting that Honey Buzzards did not base their choice of nest‐site on habitat characteristics. However, nests were placed significantly further from nests of Northern Goshawk Accipiter gentilis than would be expected if nest‐sites had been chosen at random. Furthermore, in one study area Honey Buzzards appeared to favour areas close to human settlements, perhaps indicating a mechanism to avoid Goshawks, which tend to avoid the proximity of humans. No habitat variable was significantly associated with the loss of Honey Buzzard young, but predation was higher in territories closer to breeding pairs of Goshawks at both study sites. Although Honey Buzzards are restricted to nesting in forests, their choice of nest‐site therefore appears to be largely dictated by the distribution of predators. Studies of habitat association may yield misleading results if the effects of predation risk on distribution are not considered.